An Argument for Change in Tobacco Treatment Options Guided by the ASAM Criteria for Patient Placement. Issue 5 (September 2016) - Williams, Jill M.; Steinberg, Marc L.; Kenefake, Alexandra N.; Burke, Michael V.
Abstract : Tobacco use is a major threat to public health in the United States, and the number one cause of preventable death. Although most smokers try to quit unaided, robust data indicate that pairing behavioral support to US Food Drug Administration-approved cessation medications significantly increase cessation rates. Those who do receive assistance in quitting usually receive very low intensity treatment, regardless of the severity of their dependence or their medical and environmental circumstances. This is in stark contrast to how other substance use disorders are treated, where there are varying levels of care depending on addiction severity and biopsychosocial circumstances. The American Society of Addiction Medicine (ASAM) developed a formal algorithm for assessing substance use disorders and determining the optimal level of care. The ASAM Patient Placement Criteria are regularly used to determine the appropriate level of care for all substance use disorders except tobacco. This paper will review key aspects of the ASAM dimensions of care and placement levels, with emphasis on how they apply to tobacco use and present case examples of typical smokers who would benefit from a higher intensity of tobacco dependence treatment. We also present current barriers to reimbursing healthcare providers for these services. We conclude with a commentary and discussion regarding recommendations for improvements in tobacco dependence treatment care.